Sistema inteligente de baixo custo para o monitoramento automatizado da umidade do solo - Santos, Moisés Medeiros dos (Universidade Federal Rural do Semi-Árido, 2018)
It’s very common to find irrigation practice in areas of large agricultural production, and especially of small irrigators, without the adoption of any criterion for the management of the amount of water applied. In many cases, the issues and aspects related to the soil, plant, atmosphere, as well as the skills and potentials of the irrigation system adopted in many cases not checked for any monitoring system for soil moisture. Considering the need for accessible technologies to assist the management of irrigation in the various irrigated systems, the present work developed a prototype using low cost technologies capable of monitoring soil moisture. Significantly benefiting the qualification of the irrigated production system, seeing, the viability of application in irrigation management. The first version of the in-teligente monitoring system was developed with $ 46.96. The system consists of two stations in which the data collection station (ECD) is responsible for obtaining the soil moisture parameters using sensors and transmitting it to the central data processing station (ECPD) which receives the data from and sends them to a database on the internet. The curves generated, using the potential model, from the calibration of the senses were satisfactory, presenting a good fit when the trend line coincides with the readings performed after the period when the soils reached the field capacity. The use of the system is recommended in the range between field capacity and minimum water conditions for crop survival.
Monografia
Keywords: Agricultura; Arduino; Controle de irrigação; Agriculture; Arduino; Irrigation control; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA